2019
DOI: 10.1108/ijif-06-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Interest-free monetary policy and its impact on inflation and unemployment rates

Abstract: Purpose This paper aims to examine the effects of interest-free and interest-based monetary policy on inflation and unemployment rates for two groups of countries where in one group, interest-free monetary policy (IFMP) was pursued, while in the other group, interest-based monetary policy (IBMP) was followed. Design/methodology/approach This study involves a sample of 23 developed countries divided into two groups. The authors measure economic performance by misery index (MI), and MI is calculated as unemplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…(Christiano, Eichenbaum, & Trabandt, 2016). Interest free monetary policy is proved to be better as compared to interest based policy (Selim, & Hassan, 2019).…”
Section: Islamic Banks and Employment Generationmentioning
confidence: 99%
“…(Christiano, Eichenbaum, & Trabandt, 2016). Interest free monetary policy is proved to be better as compared to interest based policy (Selim, & Hassan, 2019).…”
Section: Islamic Banks and Employment Generationmentioning
confidence: 99%
“…For example, Hamza and Saadaoui [36], Imam and Kpodar [37], and Bashir [38] found a positive relationship between the economic development of the country and the effectiveness of alternative financing. On the contrary, Selim and Hassan [39] concluded that the increase in the unemployment rate in the country would adversely affect the success of the banking industry. In addition to the studies mentioned, Kusmayadi et al [40] and Abidin and Haseeb [41] also investigated which factors affect the effectiveness of alternative financing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study by Selim and Hassan (2019) assessed the role of interest-free monetary policy on the misery index. And for the case of 12 countries, the results showed a negative effect of interest free financial expansion on misery index, which includes a decrease in inflation.…”
Section: Empirical Reviewmentioning
confidence: 99%